A high-energy and long-cycling lithium–sulfur pouch cell via a macroporous catalytic cathode with double-end binding sites - Zhao, Chen; Xu, Gui-Liang; Yu, Zhou; Zhang, Leicheng; Hwang, Inhui; Mo, Yu-Xue; Ren, Yuxun; Cheng, Lei; Sun, Cheng-Jun; Ren, Yang; Zuo, Xiaobing; Li, Jun-Tao; et al. (Nature nanotechnology, 2021)
Lithium–sulfur batteries are attractive alternatives to lithium-ion batteries because of their high theoretical specific energy and natural abundance of sulfur. However, the practical specific energy and cycle life of Li–S pouch cells are significantly limited by the use of thin sulfur electrodes, flooded electrolytes and Li metal degradation. Here we propose a cathode design concept to achieve good Li–S pouch cell performances. The cathode is composed of uniformly embedded ZnS nanoparticles and Co–N–C single-atom catalyst to form double-end binding sites inside a highly oriented macroporous host, which can effectively immobilize and catalytically convert polysulfide intermediates during cycling, thus eliminating the shuttle effect and lithium metal corrosion. The ordered macropores enhance ionic transport under high sulfur loading by forming sufficient triple-phase boundaries between catalyst, conductive support and electrolyte. This design prevents the formation of inactive sulfur (dead sulfur). Our cathode structure shows improved performances in a pouch cell configuration under high sulfur loading and lean electrolyte operation. A 1-A-h-level pouch cell with only 100% lithium excess can deliver a cell specific energy of >300 W h kg −1 with a Coulombic efficiency >95% for 80 cycles. The shuttling effect in Li–S batteries can be drastically suppressed by using a single-atom Co catalyst and polar ZnS nanoparticles embedded in a macroporous conductive matrix as a cathode. Using this strategy, Li–S pouch cells show stable cycling and high energy performances.